EFEKTIVITAS MEDIA BELAJAR INTERAKTIF PHET SIMULATION TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA DI SD - Fauzia Hairina, Rasyida; Hayati, Miswar; Aziza, Naila; Nazira, Nazwa; Suriansyah, Ahmad; Refia Rafianti, Wahdah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematics learning in elementary schools is often hampered by students' difficulty understanding non-concrete concepts. This situation requires the use of more diverse and interactive learning aids, one of which is PhET Simulation. This study aims to assess the effectiveness of PhET Simulation in influencing students' mathematics learning outcomes at the elementary school level. The method used was a literature study using a Systematic Literature Review (SLR) approach to relevant scientific articles published in the last five years. The findings of this study indicate that the use of PhET Simulation has a positive influence on the development of students' learning outcomes and understanding of mathematical concepts. In addition, the use of this media can also increase student participation and learning interest during the teaching process. Therefore, PhET Simulation can be an alternative choice of effective learning media to support mathematics learning in elementary schools.